Perilla Fruit Oil-Fortified Soybean Milk Intake Alters Levels of Serum Triglycerides and Antioxidant Status, and Influences Phagocytotic Activity among Healthy Subjects: A Randomized Placebo-Controlled Trial - Koonyosying, Pimpisid; Kusirisin, Winthana; Kusirisin, Prit; Kasempitakpong, Boonsong; Sermpanich, Nipon; Tinpovong, Bow; Salee, Nuttinee; Pattanapanyasat, Kovit; Srichairatanakool, Somdet; Paradee, Narisara (Nutrients, 2022)
This study aimed to develop perilla fruit oil (PFO)-fortified soybean milk (PFO-SM), identify its sensory acceptability, and evaluate its health outcomes. Our PFO-SM product was pasteurized, analyzed for its nutritional value, and had its acceptability assessed by an experienced and trained descriptive panel (n = 100) based on a relevant set of sensory attributes. A randomized clinical trial was conducted involving healthy subjects who were assigned to consume deionized water (DI), SM, PFO-SM, or black sesame-soybean milk (BS-SM) (n = 48 each, 180 mL/serving) daily for 30 d. Accordingly, health indices and analyzed blood biomarkers were recorded. Consequently, 1% PFO-SM (1.26 mg ALA rich) was generally associated with very high scores for overall acceptance, color, flavor, odor, taste, texture, and sweetness. We observed that PFO-SM lowered levels of serum triglycerides and erythrocyte reactive oxygen species, but increased phagocytosis and serum antioxidant activity (p < 0.05) when compared to SM and BS-SM. These findings indicate that PFO supplementation in soybean milk could enhance radical-scavenging and phagocytotic abilities in the blood of healthy persons. In this regard, it was determined to be more efficient than black sesame supplementation. We are now better positioned to recommend the consumption of PFO-SM drink for the reduction of many chronic diseases. Randomized clinical trial registration (Reference number 41389) by IRSCTN Registry.